Enhanced Staphylococcus aureus protection by uncoupling of the α-toxin-ADAM10 interaction during murine neonatal vaccination - Tomaszewski, Kelly L.; Blanchard, Meagan; Olaniyi, Reuben; Brenton, Hannah R.; Hayes, Samantha; Fatma, Farheen; Amarasinghe, Gaya K.; Cho, Byoung-Kyu; Goo, Young Ah; DeDent, Andrea C.; Fritz, Stephanie A.; Wardenburg, Juliane Bubeck (Nature communications, 2024)
Staphylococcus aureus remains a leading global cause of bacterial infection-associated mortality and has eluded prior vaccine development efforts. S. aureus α-toxin (Hla) is an essential virulence factor in disease, impairing the T cell response to infection. The anti-Hla antibody response is a correlate of human protective immunity. Here we observe that this response is limited early in human life and design a vaccine strategy to elicit immune protection against Hla in a neonatal mice. By targeted disruption of the interaction of Hla with its receptor ADAM10, we identify a vaccine antigen (Hla H 35L/ R 66C/ E 70C , Hla HRE ) that elicits an ~100-fold increase in the neutralizing anti-Hla response. Immunization with Hla HRE enhances the T follicular helper (T FH ) cell response to S. aureus infection, correlating with the magnitude of the neutralizing anti-toxin response and disease protection. Furthermore, maternal Hla HRE immunization confers protection to offspring. Together, these findings illuminate a path for S. aureus vaccine development at the maternal-infant interface. Staphylococcus aureus infection results in robust induction of immunity but the development of efficacious vaccines remains challenging. Here the authors present a vaccine that amplifies T cell immunity early in life by targeting the S. aureus α-toxin-ADAM10 interaction in a murine model.